Accuracy of non-invasive stress testing in women and men with angina in the absence of obstructive coronary artery disease. (1st May 2019) - Pargaonkar, Vedant S.; Kobayashi, Yuhei; Kimura, Takumi; Schnittger, Ingela; Chow, Eric K.H.; Froelicher, Victor F.; Rogers, Ian S.; Lee, David P.; Fearon, William F.; Yeung, Alan C.; Stefanick, Marcia L.; Tremmel, Jennifer A.
Abstract: Objective: While >20% of patients presenting to the cardiac catheterization laboratory with angina have no obstructive coronary artery disease (CAD), a majority (77%) have an occult coronary abnormality (endothelial dysfunction, microvascular dysfunction (MVD), and/or a myocardial bridge (MB)). There are little data regarding the ability of noninvasive stress testing to identify these occult abnormalities in patients with angina in the absence of obstructive CAD. Methods: We retrospectively evaluated 155 patients (76.7% women) with angina and no obstructive CAD who underwent stress echocardiography and/or electrocardiography before angiography. We evaluated Duke treadmill score, heart rate recovery (HRR), metabolic equivalents, and blood pressure response. During angiography, patients underwent invasive testing for endothelial dysfunction (decrease in epicardial coronary artery diameter >20% after intracoronary acetylcholine), MVD (index of microcirculatory resistance ≥25), and intravascular ultrasound for the presence of an MB. Results: Stress echocardiography and electrocardiography were positive in 58 (43.6%) and 57 (36.7%) patients, respectively. Endothelial dysfunction was present in 96 (64%), MVD in 32 (20.6%), and an MB in 83 (53.9%). On multivariable logistic regression, stress echo was not associated with any abnormality, while stress ECG was associated with endothelial dysfunction. An abnormal HRR was associated with endothelial dysfunction and MVD, but not an MB. Conclusion: Conventional stress testing is insufficient for identifying occult coronary abnormalities that are frequently present in patients with angina in the absence of obstructive CAD. A normal stress test does not rule out a non-obstructive coronary etiology of angina, nor does it negate the need for comprehensive invasive testing. Highlights: Conventional stress tests have poor diagnostic accuracy in patients with angina in the absence of obstructive CAD The presence of a normal noninvasive stress test does not rule out an occult coronary abnormality An abnormal heart rate recovery is associated with the presence of endothelial and microvascular dysfunction